The Microbial Contamination of Toothbrushes and Their Disinfection by Antimicrobial Solutions - Rafi A Al-Talib; Rayia J Alnaimi; Eman A Mustafa (University of Mosul, College of Dentistry, 2008)
Aims: To evaluate the bacterial survival rate on toothbrushes after brushing and the efficacy of their decontamination by immersing them in different antimicrobial solutions when toothbrushes were not in use. Materials and Methods: Twenty healthy dental students participated in this study, they were all supplied with a new toothbrush of the same brand and type together with identical tubes of fluoridated toothpastes and were asked to brush twice daily for a period of 4 weeks during which they were asked to follow their oral hygiene practices. The students were divided into 3 groups, the first group kept their toothbrushes in a ventilated area exposed to air after brushing; the second group kept their toothbrushes soaked in 1% Sodium hypochlorite solution (1 part bleach, 4 parts of distilled water); the third group immersed their toothbrushes in 0.2% chlorhexidine gluconate solution. After one month the toothbrushes were collected, decapitated and examined in the laboratory by making bacteriological cultures to identify the aerobic and anaerobic microorganisms in each toothbrush, also the total live bacterial counts per toothbrush were obtained. Results: The toothbrushes that were not immersed in any antimicrobial solution were heavily contaminated and the immersing of toothbrushes in 0. 2 % chlorhexidine gluconate solution was a very effective method in reducing the mean number of aerobic and anaerobic microorganisms. Conclusions: Toothbrushes can become contaminated after approximately 1 month of use, it is therefore recommended for individuals to use solutions like 0.2 % chlorhexidine gluconate which proved to be an effective antimicrobial agent to reduce toothbrush contamination.